The NFT handbook : how to create, sell and buy non-fungible tokens - Fortnow, Matt; Terry, Quharrison (John Wiley & Sons, Inc., 2022)
A detailed guide on how to create, sell and buy non-fungible tokens without the need for a technical background. Learn exactly what NFTs are, how they evolved, and why they have value. We'll delve into the different types and aspects of NFTs and discuss the different NFT marketplaces and the pros and cons of each. Create Your Own NFTs: Step by step instructions on all aspects of NFT creation, including what types of content to use, where to source content, adding artistic design, writing the NFT's description, adding optional unlockable content and setting an optional ongoing royalty. Mint Your NFTs: You'll learn the process of how to get your NFTs on the blockchain. Sell Your NFTs: We'll go through the whole process including creating a collection, and the different options such as setting a price or starting an auction. Buy NFTs: What you'll need to bid on and purchase NFTs, and how to avoid getting scammed. You'll also get a primer on blockchain, particularly the Ethereum cryptocurrency and "gas" fees. You'll also be shown step by step how to create, secure and fund your own cryptocurrency wallet, where you'll store your NFTs and cryptocurrency. Whether you're experienced with the blockchain and crypto or a complete noob (beginner), The NFT Handbook will guide you in the process of creating, minting, selling and buying NFTs.